Analysis Of Tax Object Selling Value (NJOP) Data Collection In Improving Land And Building (PBB) Tax Revenue Target At The Regional Revenue Agency Purwakarta District - Amalia, Dinda; Jumiati, Eti; Ata, Ata (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: This research aims to analyze NJOP data collection and how data collection capabilities can increase the achievement of PBB targets in the Bukit Indah City Purwakarta area. The data source in this research was obtained from interviews with informants who are experts in the field of land and building taxes.Design/Method/Approach: The method used is descriptive qualitative, namely describing the results of the analysis in the form of descriptions from interviews and literature reviews, as well as case studies. Analysis of research results using the NVivo 12 Plus applicationFindings: Research findings show thatThe implementation of NJOP data collection in Purwakarta district has been carried out since 2014, but NJOP data collection is still selective, namely only carried out in several areas/areas of Bukit Indah City/Besland (BIC) and surrounding areas.Achievement of PBB targets at the Purwakarta Regency Regional Revenue Agency, to dateThe Purwakarta district government has made efforts to increase PBB P2 revenues in particular, by providing regulations to facilitate Bapenda's activities.Â Â